E-WOM’s Impact on Purchase Intention Through Brand Awareness and Perceived Quality - Puspadini , Alifa; Hidayat, Muhammad Sondang; Khasanah, Imroatul; Yoestini (Economic and Business Horizon, 2025)
Electronic Word of Mouth (E-WOM) has become a strategy widely adopted by companies to promote their products, especially in line with the advancement of the digital era. Businesses continue to strive to maintain strong engagement with customers. This study examines the effect of E-WOM on consumer purchase intention, with brand awareness and perceived quality as mediating variables (case study on Sea Makeup cosmetic products in a region). These variables include E-WOM as an independent variable, brand awareness and perceived quality as mediators, and purchase intention as the dependent variable. The sample consisted of 135 female respondents aged 16–54 years in Semarang who knew or had purchased Sea Makeup products. Data were collected through purposive non-probability sampling using a questionnaire. Structural Equation Modeling (SEM) with AMOS was used for the analysis. The findings indicate that E-WOM positively influences brand awareness and perceived quality, both of which in turn positively influence purchase intention. E-WOM also has a direct impact on purchase intention positively.